ANALISIS PEMASARAN KAKAO DI KECAMATAN BACAN TIMUR, KABUPATEN HALMAHERA SELATAN - Eljan Gilbert Maniku; Joachim Noch Karel Dumais; Lyndon Reindhart Jacob Pangemanan (AGRI-SOSIOEKONOMI, 2021)
The objective of this research is to analyze marketing channels, functions of marketing institutions, profit margin, marketing margins, farmer's share and cocoa marketing efficiency in East Bacan District, South Halmahera Regency. This research was conducted from June to August 2021. The sampling method of farmers used purposive sampling. The number of farmer respondents is 39 people and the sample is taken by traders using snowball sampling. The data analysis used is descriptive qualitative and quantitative analysis. The results showed that there were III (three) marketing channels. The functions of marketing institutions carried out by marketing agencies are exchange functions, physical functions, and facilities functions. The total margin of marketing channel I is Rp. 4,000/Kg, marketing costs of Rp. 2.700/Kg and a profit margin of Rp. 1300/Kg. The total margin for channel II is Rp. 5000/Kg, marketing costs of Rp. 2.350/Kg and a profit margin of Rp. 2.650/Kg. The total margin of marketing channel III is Rp. 7,500/Kg, marketing costs of Rp.2,950/Kg and profit margin of Rp. 4.575/Kg. Farmer's share obtained in channel I is 86.20%. channel II by 82.14%. and channel III of 73.68%. The value of the efficiency of marketing channel I is 9.31% <50%. The value of the efficiency of marketing channel II is 8.39% < 50%. The value of the efficiency of marketing channel III is 10.26% <50%. In terms of efficiency, the three marketing channels are already efficient and marketing channel II is the most efficient marketing channel compared to channels I and III.